1980
DOI: 10.1099/00221287-119-2-341
|View full text |Cite
|
Sign up to set email alerts
|

Protoplasts from Yeast and Mycelial Forms of Candida albicans

Abstract: Protoplasts have been obtained in high yields from the yeast and mycelial forms of a variety of strains of Candida albicans by enzymic digestion of cells with commercially available lytic enzymes. The protoplast formation procedure was equally effective for exponential and stationary phase cells. Pretreatment with dithiothreitol and Pronase in the presence of EDTA and Tris was necessary. Other thiol reagents and conditions did not release protoplasts from all the strains of C. albicans tested. Treatment with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The Candida albicans mitochondrial genome is a circle of about 40 kilobase pairs (15). The circular molecule contains a large inverted duplication analogous to that found in almost all chloroplast DNAs (14), in some other mitochondrial DNAs (mtDNAs) (7,16), and in other isolated instances.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Candida albicans mitochondrial genome is a circle of about 40 kilobase pairs (15). The circular molecule contains a large inverted duplication analogous to that found in almost all chloroplast DNAs (14), in some other mitochondrial DNAs (mtDNAs) (7,16), and in other isolated instances.…”
mentioning
confidence: 99%
“…We have previously reported the cloning of five of the six EcoRI restriction fragments by ligating a mixture of pBR322 DNA and whole mtDNA from C. albicans H317, both cleaved with EcoRI (15). This procedure did not yield a clone containing the largest fragment, El.…”
mentioning
confidence: 99%
“…As mentioned above, physicochemical properties are different between growing and non-growing zones, and structural and chemical differences have also been noticed. In a series of papers, Wessels and co-workers (159,215,217,218,240), have also clearly established that newly-synthesized ~(1-3) glucans present in the apical region are watersoluble and that after some time they become insoluble in water and then insoluble in alkali. It has been observed that the apical region of S. commune does not contain chitin microfibrils and that the polysaccharide is extremely sensitive to chitinase degradation and dissolution with dilute Hel, whereas in the non-growing zone or in dead hyphae, microfibrils are readily observed and chitin becomes resistant to the above mentioned treatments (232).…”
Section: Cell Wall Expansionmentioning
confidence: 98%
“…As previously noted, efficient protoplast formation in C. albicans requires the use of S-S reducing agents, followed by proteases and l3-glucanases (78,101,240). Cell wall regeneration in C. albicans, in partial contrast to S. cerevisiae, occurs in simple liquid media.…”
Section: Cell Wall Morphogenesis During Protoplast Regenerationmentioning
confidence: 98%
See 1 more Smart Citation